2019
DOI: 10.1021/acsapm.9b01070
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linkable Fluorinated Polynorbornene with High Thermostability and Low Dielectric Constant at High Frequency

Abstract: A fluorinated polymer with high thermostability and low dielectric constant was synthesized through the ring-opening metathesis polymerization (ROMP) and a postpolymerization. Casting a solution of the polymer gave a flexible free-standing film, which was treated at high temperature to give a cross-linked network, displaying the transmittance of up to 92% and a water contact angles of more than 100°. The cross-linked networks also displayed low dielectric constant (D k) of 2.39 and dissipation factor (D f) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…It was found in our investigations that the polysiloxanes containing perfluorocyclobutane groups exhibit good dielectric properties, especially, they display low D k and D f at a high frequency of 5 G or 10 GHz. [11][12][13][14] However, such a type of the polymers is somewhat difficult to be prepared because they are derived from the trifluorovinyl ether monomers, [15,16] which are not easily obtained. It is noted that many trifluoromethyl-containing molecules are commercially available and their derivatives are also easily prepared.…”
mentioning
confidence: 99%
“…It was found in our investigations that the polysiloxanes containing perfluorocyclobutane groups exhibit good dielectric properties, especially, they display low D k and D f at a high frequency of 5 G or 10 GHz. [11][12][13][14] However, such a type of the polymers is somewhat difficult to be prepared because they are derived from the trifluorovinyl ether monomers, [15,16] which are not easily obtained. It is noted that many trifluoromethyl-containing molecules are commercially available and their derivatives are also easily prepared.…”
mentioning
confidence: 99%
“…[9,10] Therefore, most studies reported in recent years have focused on the hightemperature resistant polymeric dielectric materials with excellent heat resistance and stability of thermal movement of molecular chains. [11][12][13][14] To develop various high-temperature resistant, low dielectric constant, and low dielectric loss polymeric materials with different structures, many efforts have been done including the introduction of cross-linked network into molecular chain [15][16][17][18][19][20][21][22][23] and the promotion of thermal conductivity. [24][25][26] Fluorinated poly(aryl ether) (FPAE), as high performance polymeric material, [27,28] has been widely studied owing to their high thermal stability, excellent mechanical strength, and low dielectric constant.…”
Section: Doi: 101002/marc202000100mentioning
confidence: 99%
“…[ 9,10 ] Therefore, most studies reported in recent years have focused on the high‐temperature resistant polymeric dielectric materials with excellent heat resistance and stability of thermal movement of molecular chains. [ 11–14 ] To develop various high‐temperature resistant, low dielectric constant, and low dielectric loss polymeric materials with different structures, many efforts have been done including the introduction of cross‐linked network into molecular chain [ 15–23 ] and the promotion of thermal conductivity. [ 24–26 ]…”
Section: Figurementioning
confidence: 99%
“…Additionally, because the atomic radius and electronegativity of fluorine atoms are larger, the introduction of C−F bonds can also increase the free volume and reduce the polarizability of polymers. 9,15,32,37,38 Therefore, to realize the utilization of biomass resource rosin, it has aroused our great interest to develop low-k materials with good mechanical properties and hydrophobicity by introducing hydrogenated phenanthrene rings and C−F bonds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Rosin acid contains a bulky hydrogenated phenanthrene ring structure, and its molecular polarity and rigidity are similar to those of cyclic aliphatic and aromatic compounds. In particular, the structure of the hydrogenated phenanthrene ring is larger than that of the benzene ring, and thus, it is speculated that introducing hydrogenated phenanthrene rings can better increase free volume. Additionally, because the atomic radius and electronegativity of fluorine atoms are larger, the introduction of C–F bonds can also increase the free volume and reduce the polarizability of polymers. ,,,, Therefore, to realize the utilization of biomass resource rosin, it has aroused our great interest to develop low- k materials with good mechanical properties and hydrophobicity by introducing hydrogenated phenanthrene rings and C–F bonds.…”
Section: Introductionmentioning
confidence: 99%